The Effect of The Use of Integrated Social Welfare Data, Information Technology, and Internal Control Systems on The Prevention of Fraud in The Management of Social Assistance Funds - Moh Alamsyach Soleman; Mahdalena Mahdalena; Siti Pratiwi Husain (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the impact of the use of the Integrated Social Welfare Data (DTKS) and the Internal Control System (SPI) on fraud prevention in the management of social assistance funds at the Gorontalo Provincial Social Affairs Office. Research Method: This study employed a quantitative approach with a causal design. Primary data were collected through a questionnaire distributed to employees directly involved in the administration of social assistance, who were selected using purposive sampling. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the aid of SPSS. Results and Discussion: The research results show that the use of the DTKS does not have a significant effect on fraud prevention. These findings indicate that the existence of the DTKS is not yet capable of directly preventing fraud if data quality, updates, and verification of aid recipients are not yet optimal. In contrast, the SPI has a positive and significant effect on fraud prevention. Together, the DTKS and SPI have a significant effect on fraud prevention, with an Adjusted R² value of 0.778. Implications: Strengthening the SPI, improving the quality of DTKS data, and optimizing the verification and validation processes are necessary to support accountable and targeted social assistance management. Originality: This study positions the DTKS as a social welfare database, an information system, and an administrative verification tool for preventing fraud in the management of social assistance.